Reducing inpatient falls in a 100% single room elderly care environment: evaluation of the impact of a systematic nurse training programme on falls risk assessment (FRA) - Singh, Inderpal (BMJ Qual Improv Rep, 2016)
Inpatient falls (IF) are the most commonly reported safety incidents. The high rate of inpatient falls was reported in a newly built hospital, within Aneurin Bevan University Health Board, Wales (UK). The aim of the project is to reduce the incidence of IF and associated adverse clinical outcomes in a hospital with 100% single rooms. The key mechanism for improvement was education and training of nursing staff around falls risk factors. A Plan-Do-Study-Act methodology was used and a geriatrician-led, systematic nurse training programme on the understanding and correct use of existing multifactorial falls risk assessment (FRA) tool was implemented in April 2013. Pre-training baseline data revealed inadequate falls assessment and low completion rates of the FRA tool. Subsequent, post-training data showed improvement in compliance with all aspects of FRA. Concurrent with nurse training, the actual falls incidence/1000 patient-bed-days fell significantly from the baseline of 18.19±3.46 (Nov 2011-March 2013) to 13.36±2.89 (p<0.001) over next 12 months (April 2013-March 2014) and remained low (mean falls 12.81±2.85) until November 2015. Improved clinical outcomes have been observed in terms of a reduction of length of stay and new care home placements, making total annualised savings of £642,055.